The Effects of Reciting Al-Qur’an(Ruqyah Syar’iyyah) on Sleep Qualityof Elderly People Living in a Nursing Home - Mardiyanti Mardiyanti; Ita Yuanita; Sherly Mulya Pratiwi; Wahyudi Widada (TSAQAFAH, 2024)
Context/Purpose: Elderly are at risk of having poor sleep quality due to chronic illness, emotional distress, anxiety, environment, malnutrition and low physical activities. Evidence showed islamic spiritual therapy effectively improve mental health, reduce anxiety and depression. However, the use of ruqyah syar’iyyah for improving sleep quality due to mental health problems has not been studied well, therefore this research aimed to investigate the effectiveness of ruqyah therapy on sleep quality of elderly people living in a nursing home with mental health problems. Methods: This study used Quasi Experimental with one group Pre-test Post-test design approach. Elderly in the nursing homes were purposively selected based on their Pittsburgh Sleep Quality Index (PSQI) score. Seventeen elderly met the inclusion criteria (PSQI score above 5, Muslim, able to read Qur’an, and followed all the research stages) and they were trained how to perform ruqyah syar’iyyah. The intervention was delivered by reciting selected Surah in the Qur’an once a day for three nights. The post-test was held on the last day of data collection by measuring PSQI. Results: The age of respondents range from 61 to 82 years old with the majority at the elderly age (60- to 74-year-old at 76,5%), most of the education level of the respondents were elementary school (64,7%). The PSQI mean score was 14,88 ± 2,09 (pre-test) vs 9.12 ± 1,6 (post-test) P-value<0.05. Interpretation: The mean PSQI score significantly decreased after the ruqyah syar’iyyah intervention, indicating an improvement in sleep quality. The recitation of specific verses from the Qur’an is seen as a source of tranqulity and relief, potentially helping the elderly cope with anxiety and loneliness. However, this research excluded the cause of poor quality of sleep of the elderly, therefore further research investigating the cause of poor sleep quality of the elderly in the nursing homes with larger studies are needed to validate the effectiveness of Ruqyah Syar’iyyah in managing sleep disturbances in the elderly. Conclusion: Nurses and other heathcare providers are suggested to use Ruqyah syar’iyyah therapy for intervening poor sleep quality among elderly, especially in the nursing home.